Assessing changes in atmospheric rivers under stratospheric aerosol injection using ARISE-SAI-1.5 - Kwesi T Quagraine; Travis A O’Brien; Kwesi A Quagraine; Ben Kravitz; Simone Tilmes (Environmental Research: Climate)
In a warming climate, where climate adaptation and mitigation strategies are increasingly critical, understanding changes in major global atmospheric moisture transport mechanisms, such as atmospheric rivers (ARs), is essential for assessing shifts in the hydrological cycle. This study examines the frequency and impacts of ARs under the shared socioeconomic pathway (SSP2-4.5) warming scenario and the stratospheric aerosol injection (SAI) scenario (ARISE-SAI-1.5). Our findings indicate that under SAI-1.5, ARs retreat from inland regions, and the occurrence of high-impact ARs (Category 3 and above) decreases, although some uncertainty remains regarding the response time of ARs to SAI. However, under future climate without SAI (SSP2-4.5), ARs penetrate further inland and there are higher numbers of high-impact ARs ( $ \gt $ Category 3 ARs). In the northern hemisphere oceans, SAI-1.5 leads to a gradual increase in AR frequency compared to SSP2-4.5, whereas the southern hemisphere oceans exhibit the opposite trend. Also, extreme AR-associated precipitation is reduced under SAI-1.5 relative to SSP2-4.5, whereas beneficial precipitation is projected to increase under SAI-1.5. The contrasting responses associated with AR location and intensity highlights the need for further research to better understand the underlying drivers of AR changes before SAI can be considered in policy decisions affecting global moisture transport mechanisms.